Tryptophan-Catabolizing Enzymes – Party of Three - Ball, Helen J.; Jusof, Felicita F.; Bakmiwewa, Supun M.; Hunt, Nicholas H.; Yuasa, Hajime J. (Frontiers in Immunology, 2014)
Indoleamine 2,3-dioxygenase (IDO) and tryptophan 2,3-dioxygenase (TDO) are tryptophan-degrading enzymes that have independently evolved to catalyze the first step in tryptophan catabolism via the kynurenine pathway. The depletion of tryptophan and formation of kynurenine pathway metabolites modulates the activity of the mammalian immune, reproductive and central nervous systems. IDO and TDO enzymes can have overlapping or distinct functions depending on their expression patterns. The expression of TDO and IDO enzymes in mammals differs not only by tissue/cellular localization but also by their induction by distinct stimuli. To add to the complexity, these genes also have undergone duplications in some organisms leading to multiple isoforms of IDO or TDO. For example, many vertebrates, including all mammals, have acquired two IDO genes via gene duplication, although the IDO1-like gene has been lost in some lower vertebrate lineages. Gene duplications can allow the homologs to diverge and acquire different properties to the original gene. There is evidence for IDO enzymes having differing enzymatic characteristics, signaling properties and biological functions. This review analyses the evolutionary convergence of IDO and TDO enzymes as tryptophan-catabolizing enzymes and the divergent evolution of IDO homologs to generate an enzyme family with diverse characteristics not possessed by TDO enzymes, with an emphasis on the immune system.